Revisiting the narrative theory of genres: Critiquing Jürgen Habermas's Communicative Action - Singh Sharanpal; Goyal Shilpi (Journal of Language and Cultural Education)
The world is deeply connected through narratives, which enrich its stories and meanings. Tales about others and us bring vibrancy to life, making existence more dynamic. Critical Discourse Studies analyse these narratives, with the Discourse Historical Approach being a prominent method. This approach emphasises the centrality of narratives while integrating elements like comedy, tragedy, irony, and romance, as suggested by Frye. Such integration not only enhances causality, an essential aspect of textual analysis but also ensures that other essential features like conflict remain significant. By combining social dimensions with storytelling, this approach offers a more profound understanding of narratives. Habermas's theory of communicative action plays a vital role here, enhancing the semantic depth of the Discourse Historical Approach. It provides a solid foundation for analysing genres and narratives, making the process more authentic and insightful. Together, these methods create a robust framework for exploring how stories shape meaning and enrich discourse.